Raise : what 4-H teaches seven million kids and how its lessons could change food and farming forever - Butler, Kiera, 1980- (University of California Press, 2014)
When Kiera Butler visits a county fair for the first time, she is captivated by the white-uniformed members of the 4-H club and their perfectly groomed animals. She sets off on a search for a "real" 4-H'er, a hypothetical wholesome youth whom she imagines wearing cowboy boots and living on a ranch. Along the way, she meets five teenage 4-H'ers from diverse backgrounds and gets to know them as they prepare to compete at the fair. Butler's on-the-ground account of the teens' concerns with their goats, pigs, sheep, proms, and SAT scores is interwoven with a fascinating history of the century-old 4-H club as it solicits corporate donations from top agribusiness firms such as DuPont, Monsanto, and Cargill. Her quest takes her from California's cities and suburbs all the way to Ghana, where she investigates 4-H's unprecedented push to expand its programs in the developing world -- and the corporate partnership that is supporting this expansion. Raise combines vivid accounts from a little-known subculture with a broader analysis of agriculture education today, using 4-H as a lens through which to view the changing landscape of farming in America and the rest of the world